New empirical evidence on the impact of public debt on economic growth in EMU countries - Sosvilla, Simon; Gómez-Puig, Marta (Revista de Economía Mundial, 2019)
New empirical evidence is presented on the impact of public debt on economic growth. To that end, we employ the Autoregressive Distributed Lag (ARDL) bounds testing approach using annual data from both central and peripheral countries of the European Economic and Monetary Union (EMU) for the 1961-2013 period. In particular, we allow for different endogenously (data-based) regimes in the parameter relating the public debt variable to the real growth rate. Our results suggest that the impact of public debt on economic growth not only changes across EMU countries, but also over time.